Phytochemical Profiling, Cytotoxicity, and Antiproliferative Potential of Solenostemon monostachyus (Fabaceae) Leaves - Odion, Emmanuel Eimiomodebheki; Ambe, Daniel Akpe-Efiak; Ifejika, Kidochukwu Naomi; Odiete, Eravweroso Congrat; Osigwe, Chinyelu Clementina (Sciences of Phytochemistry, 2024)
Solenostemon monostachyus (S. monostachyus) is a widely distributed and important herb in central and west Africa, traditionally used in treating various ailments, including tumors. This study aims to identify the phytoconstituents in the methanol leaf extract of S. monostachyus and evaluate the cytotoxic and anti-proliferative potentials of the methanol extract and its fractions (n-hexane, dichloromethane, and ethyl acetate). Preliminary phytochemical screening was conducted to determine different classes of phytochemical constituents in the powdered leaf. Phytoconstituents were identified from the methanol extract by chromatographic analysis (HPLC and GC-MS). The extract and fractions of S. monostachyus were tested against Raniceps raninus tadpoles and Sorghum bicolor radicles to evaluate their cytotoxic and growth suppression potentials. HPLC analysis revealed catechin, cyanogenic glycosides, flavanone, sparteine, sapogenin, and phytate. GC-MS analysis displayed (Z)-2,3-dihydroxypropyl 9-octadecenoic acid ester, 2-dodecyl-1,3-propanediol, 1-nitro-bicyclo[6.1.0]nonan-2-one, and furazano[3,4-b]pyrazine-5,6-diamine, N, N’-di(propynyl) as the prominent compounds. A cytotoxic effect was observed at 160 µg/mL, with a recorded 56.67 ± 3.33% mortality within 0.5 h, increasing to 100.00 ± 0.00% mortality of the tadpoles within 1 h of treatment. A concentration of 16 mg/mL of S. monostachyus extract significantly (p<0.05) exerted 56.15% (0.82 ± 0.08) suppression of the emerging radicles in 24 h, which later increased to 94.55% (1.10 ± 0.07) after 96 h. This indicates that S. monostachyus leaf extract contains phytochemicals with cytotoxic and growth-suppression potentials.